Strategi Komunikasi Pemasaran Halal Tourism Pantai Pulau Santen Banyuwangi (GEMA EKONOMI, 2023)
This study aims to find out and analyze the marketing mix strategy and marketing communications that have been carried out by the Culture and Tourism Office of Banyuwangi Regency and the Management or Awareness Group of Pulau Santen Beach Tourism in Banyuwangi to introduce and increase public interest in visiting tourist destinations that carry the theme of halal tourism on Pulau Santen Beach. Banyuwangi. This research is a qualitative research with a case study approach. The research technique is carried out by observing and interviewing predetermined informants. The results of the study show that halal tourism on Pulau Santen Banyuwangi Beach has carried out a good marketing mix strategy, namely unique products with the theme of halal tourism, affordable entry ticket prices, easily accessible tourist sites with large parking facilities as well as promotion and marketing communications carried out through public relations, online marketing via Instagram and Facebook as well as advertising by placing banners in locations that are easy for the public to read